The Dynamics of Paranoid Schizophrenia Outpatients at Clinic X and Its Benefits to Humans - Jelite Prenggo Putri; Johanna Natalia (Budapest International Research and Critics University, 2022)
Schizophrenia is a mental disorder with positive, negative, cognitive, affective, and aggressive symptoms. Negative stigma against individuals with schizophrenia impacts on opportunities to exist in a social environment. This stigma also causes people with schizophrenia to withdraw from the environment, feel a sense of hopelessness and anxiety. The purpose of this study is to recognize the dynamics of outpatients with schizophrenia of paranoid sub-type at Clinic X. One person is the participant in this study with the selection criteria of purposive sampling method. This research uses case study method. The assessment carried out in this study employs the methods of observation, interviews, and psychological tests. The result of this study indicates that parenting style can impact behavior and mental health such as schizophrenia disorder. The condition of individual with schizophrenia disorder of paranoid sub-type can improve through supports from the surrounding environment, especially family members, with regular medication consumption. Meanwhile, the condition may get worse due to immature thinking patterns and a rigid attitude.